Pengaruh Disiplin Kerja Motivasi Kerja dan Kepuasan Kerja terhadap Kinerja Pegawai pada PT Bank Pembangunan Daerah Bali Cabang Renon - Putu Ayu Yuni Puji Astuti; Nyoman Andika Triadhi; I Gusti Putu Agung Widya Goca (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
A key determinant of organizational success, particularly in the banking industry, is employee performance; employees are expected to deliver services that are fast, accurate, professional, and focused on customer satisfaction. Preliminary observations and interviews at the Renon Branch of PT Bank Pembangunan Daerah Bali revealed various issues indicating suboptimal employee performance, such as administrative errors, delays in task completion, inconsistent understanding of changes in work procedures, and disparities in responsibility levels and adaptability when performing duties. This study aims to examine how employee performance at the Renon Branch of PT Bank Pembangunan Daerah Bali is influenced by work discipline, motivation, and job satisfaction. The study employs a survey design and a quantitative methodology. A census sampling technique was used, involving all 44 permanent employees as respondents. Descriptive statistics and multiple linear regression analysis were utilized to analyze data collected through observation, interviews, documentation, and Likert-scale questionnaires. The findings indicate that employee performance is positively and significantly influenced by work motivation, work discipline, and job satisfaction. These three factors also exert a significant positive influence on employee performance when considered collectively. The results suggest that management can effectively enhance employee performance, service quality, and the competitiveness of the Renon Branch of PT Bank Pembangunan Daerah Bali by implementing an integrated approach to improve work discipline, work motivation, and job satisfaction.